PB28, the Sigma-1 and Sigma-2 Receptors Modulator With Potent Anti–SARS-CoV-2 Activity: A Review About Its Pharmacological Properties and Structure Affinity Relationships - Abate, Carmen; Niso, Mauro; Abatematteo, Francesca Serena; Contino, Marialessandra; Colabufo, Nicola Antonio; Berardi, Francesco (Frontiers in Pharmacology, 2020)
These unprecedented times have forced scientific community to gather in order to face COVID-19 pandemic. Efforts in diverse directions have been made, while a multi-university team has focused the attention on the identification of the host (human) proteins interacting with SARS-CoV-2 viral proteins, with the aim of hampering these interactions that may cause the severe COVID-19 symptoms. Sigma-1 and sigma-2 receptors surprisingly belong to the ‘druggable’ host proteins found, and the pan-sigma receptors modulator PB28 displays the most potent anti SARS-CoV-2 activity in in vitro assays. Being 20-fold more active than hydroxychloroquine, without cardiac side-effects, PB28 is a promising antiviral candidate worthy of further investigation. Our research group first developed PB28 in 1996 and since thereafter, the compound was thoroughly characterized in its biological properties, while becoming our lead compound for Structure Affinity Relationship (SAfiR) studies at the sigma receptor subtypes. We herein report our knowledge about PB28, in order to share information that may help to gain insights into the antiviral action of this compound and sigma receptors, while providing structural hints that may speed up the translation into therapeutics of this class of ligands.